Exhaust Emission Control in Sport Motorcycles: A Comparison of Catalytic Converters with Alternative Metal Materials - Warju, Warju; Ariyanto, Sudirman Rizki; Pratama, Muhammad Yandi (Jurnal Polimesin, 2024)
In this modern era, motor vehicles have brought significant changes in human life. Faster and more efficient mobility has increased connectivity between regions, supported economic growth, and improved quality of life. However, increased mobility also means an increase in vehicle exhaust emissions, which contribute to climate change and air pollution. One effective technology for controlling exhaust emissions is the use of catalytic converters. Metal catalytic converters, such as copper, brass, and chrome-plated copper, have been researched as more affordable and effective catalyst alternatives. This research aims to analyze the optimal design of exhaust systems with catalytic converters among three types of alternative materials (copper, brass, and chrome-plated copper) as well as standard exhaust systems without catalysts (STD NC) and standard platinum group metal exhaust systems (STD PGM) in maximizing the reduction of motor vehicle exhaust emissions. An experimental research design was used by utilizing a 2015 Yamaha Vixion Lightning as the research object. Catalytic converters were prepared with specific specifications to ensure consistency and accuracy in measurements. CO (carbon monoxide), HC (hydrocarbons), CO2 (carbon dioxide), and O2 (oxygen) emissions were analyzed using an Exhaust Gas Analyzer. The research results indicate that the CuCr sample exhibits excellent performance in reducing CO and HC emissions. The CuCr sample has an average CO emission of 4.09% Vol with a standard deviation of 1.46, demonstrating good consistency in CO emissions. Meanwhile, the average HC emissions from the CuCr sample are 320 ppmVol with a standard deviation of 106, indicating good consistency in HC emissions. All samples meet the emission standards set by the government, except for the STD NC sample, which exceeds the CO emission threshold.